LITERATURE REVIEW: PERAN PENTING MANAJEMEN SDM DI DALAM ORGANISASI DI ERA COVID-19 - Mahi Datun Soliha; Hanung Eka Atmaja (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
The study aims to determine the importance of human resource management in an organization in the covid 19 era. The method in this study uses research methods. From the explanation, it can be said that the importance of HR management in organizations in the COVID-19 era, namely human resource management, has three functions, namely operational functions, managerial functions, and functions to realize organizational goals in an integrated manner. The human resources department acts as a mediator between the organization, employees, and employers. To be able to prosper for both parties, they must carry out their functions as well as possible. The HR strategy that has been carried out during the pandemic and new normal uses three ways, namely running remote work, managing employee productivity, and upskilling for digital. One of the procedures used in developing the knowledge and skills of employees is training. While development is an educational process. Termination of employment is the last and unavoidable option from the impact of the covid 19 pandemic. Planning will provide effective and efficient results by following good HR planning in organizational goals.